A Measurement of the CMB {\ltEE\gt Spectrum from the 2003 Flight of BOOMERANG} - Montroy, TE; Ade, PAR; Bock, JJ; Bond, JR; Borrill, J; Boscaleri, A; Contaldi, CR; Crill, BP; de Bernardis, P; de Oliveira Costa, A; di Stefano, G; Hivon, E; et al. (The Astrophysical Journal, 2006)
We report measurements of the CMB polarization power spectra from the 2003 January Antarctic flight of BOOMERANG. The primary results come from 6 days of observation of a patch covering 0.22% of the sky centered near R.A.=82.5d, decl.=-45$^{deg$. The observations were made using four pairs of polarization-sensitive bolometers operating in bands centered at 145 GHz. Using two independent analysis pipelines, we measure a nonzero \ltEE\gt signal in the range 201\ltl\lt1000 with a significance of 4.8 $σ$, a 2 $σ$ upper limit of 8.6 $μ$K$^2$ for any \ltBB\gt contribution, and a 2 $σ$ upper limit of 7.0 $μ$K$^2$ for the \ltEB\gt spectrum. Estimates of foreground intensity fluctuations and the nondetection of \ltBB\gt and \ltEB\gt signals rule out any significant contribution from Galactic foregrounds. The results are consistent with a $Λ$CDM cosmology seeded by adiabatic perturbations. We note that this is the first detection of CMB polarization with bolometric detectors. }